2015
DOI: 10.1175/jhm-d-14-0216.1
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Wind-Induced Losses from a Precipitation Gauge Network in the Australian Snowy Mountains

Abstract: Wind-induced losses, or undercatch, can have a substantial impact on precipitation gauge observations, especially in alpine environments that receive a substantial amount of frozen precipitation and may be exposed to high winds. A network of NOAH II all-weather gauges installed in the Snowy Mountains since 2006 provides an opportunity to evaluate the magnitude of undercatch in an Australian alpine environment. Data from two intercomparison sites were used with NOAH II gauges with different configurations of wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 25 publications
3
29
0
Order By: Relevance
“…Interestingly, the relative bias was reduced for higher precipitation amounts. This is consistent with Chubb et al (2015), who found that undercatch was reduced for higher precipitation rates (other factors being equal). It may also reflect the tendency for very heavy precipitation to be in the form of rain rather than snow, making the precipitation measurement less affected by wind speed (Chubb et al, 2015).…”
Section: Accuracy Of the Awap Rainfall Analysis In The Snowy Mountainssupporting
confidence: 92%
See 4 more Smart Citations
“…Interestingly, the relative bias was reduced for higher precipitation amounts. This is consistent with Chubb et al (2015), who found that undercatch was reduced for higher precipitation rates (other factors being equal). It may also reflect the tendency for very heavy precipitation to be in the form of rain rather than snow, making the precipitation measurement less affected by wind speed (Chubb et al, 2015).…”
Section: Accuracy Of the Awap Rainfall Analysis In The Snowy Mountainssupporting
confidence: 92%
“…This is consistent with Chubb et al (2015), who found that undercatch was reduced for higher precipitation rates (other factors being equal). It may also reflect the tendency for very heavy precipitation to be in the form of rain rather than snow, making the precipitation measurement less affected by wind speed (Chubb et al, 2015). Figure 7a shows the spatial distribution of the mean May-September precipitation amount derived using the Barnes analysis procedure described above and gauge data from both the BOM and SHL.…”
Section: Accuracy Of the Awap Rainfall Analysis In The Snowy Mountainssupporting
confidence: 92%
See 3 more Smart Citations